A Bibliometric Mapping on Maqasid Shariah in Islamic Perspective - Lia Fitria; Nabilatul Hija; Muhammad Arsyi; Shabrina Kasyifa Firdausi (SMART Insight, 2022)
This research aims to find out how much research on maqasid sharia and its coverage based on journals published with the theme